Trypanosoma evansi as a Major Cause of Animal Trypanosomiasis: A Comprehensive Review - Warsito, Sunaryo Hadi; Khairullah, Aswin Rafif; Lamid, Mirni; Al-Arif, Mohammad Anam; Hermadi, Herry Agoes; Lokapirnasari, Widya Paramita; Kusala, Muhammad Khaliim Jati; Wibowo, Syahputra; Ayuti, Siti Rani; Wardhani, Bantari Wisynu Kusuma; Fauziah, Ima; Yanestria, Sheila Marty; Moses, Ikechukwu Benjamin; Prasetyo, Agung; Aryaloka, Suhita; Fauzia, Kartika Afrida; Ahmad, Riza Zainuddin; Kurniasih, Dea Anita Ariani (Universitas Airlangga, 2025)
Trypanosomiasis caused by Trypanosoma evansi is a major protozoan illness that affects animals worldwide. It is also referred to as “surra” and affects a variety if wild and domestic animals such as sheep, cattle, goats, dogs, buffaloes, pigs, elephants, amongst others. In preparing this review, relevant scientific articles were searched on PubMed, SCOPUS, and Web of Science databases using the keyword “Trypanosoma evansi AND animals”. T. evansi are carried by a vast number of hematophagous flies and are found in the extracellular and internal fluids of certain hosts. Trypanosomosis is mostly characterized by anemia, and the degree of anemia can typically be used as a gauge for the disease's severity. Trypanosomiasis compromises the host animal's immune system and its diagnosis is dependent on a number of factors such as thorough clinical examination, suitable sample collection, sample size, suitable diagnostic test performance, and logical interpretation of test results. The clinical manifestations of trypanosomiasis vary widely in both appearance and severity, ranging from neurological disturbances and skin plaques to vaginal enlargement. Hematophagous biting flies, including Tabanus, Haematopota, Glossina, Chrysops, Lyperosia, Stomoxys, and Hippobusca flies, contribute to the spread of trypanosomiasis. Four medications are primarily used to treat trypanosomiasis: quinapyramine, karetin, diminazene aceturate (Berenil), and melarsomine (cymelarsan). An efficient vaccination program is an additional technique for managing infectious diseases in addition to treatment. The most important step in curtailing the spread of trypanosomiasis caused by T. evansi is to stop its transmission by flies via physical and chemical methods.